Homeopathic Treatment of a Lower Leg Edema—A Case Report - Pannek, Jürgen; Pannek-Rademacher, Susanne (Homeopathy, 2021)
Background Homeopathy is frequently and successfully used in daily clinical practice, so there is a need for well-documented case reports that illustrate its effectiveness. For this reason, we present a case in which homeopathy was used to treat an ankle and lower leg for spontaneous acute swelling and redness.Case Report A 54-year-old man presented with recurrence of a swollen left ankle and lower leg, which had previously been treated by conventional medicine. After case taking, a homeopathic treatment with Apis mellifica 200c led to a fast improvement. The patient was free of symptoms within 24 hours and has remained so for 3 years.Conclusion Homeopathic treatment with Apis mellifica led to a fast and long-lasting improvement of an acute ankle swelling and reddening that had recurred after conventional medical therapy of similar symptoms.
Keywords: Apis mellifica; case report; edema; homeopathy